2012
DOI: 10.1002/clc.22000
|View full text |Cite
|
Sign up to set email alerts
|

Erroneous Computer Electrocardiogram Interpretation of Atrial Fibrillation and Its Clinical Consequences

Abstract: Background: The aim of this study was to determine the frequency and nature of errors made by computer electrocardiogram (ECG) analysis of atrial fibrillation (AF), and the clinical consequences. Hypothesis: Computer software for interpreting ECGs has advanced. Methods: A total of 10279 ECGs were collected, automatically interpreted by the built-in ECG software, and then reread by 2 cardiologists. AF-related ECGs were classified into 3 groups: overinterpreted AF (rhythms other than AF interpreted as AF), misin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 11 publications
(8 reference statements)
4
24
0
Order By: Relevance
“…However, this exam has certain limitations with inappropriate arrhythmia diagnosis due to built-in software. Reports describe 7.8% of error in clinical cases, especially when events of atrial fibrillation occur (Bae et al 2012). Therefore preliminary software interpretations require reading and confirmation by a qualified eletrocardiographer (Estes 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, this exam has certain limitations with inappropriate arrhythmia diagnosis due to built-in software. Reports describe 7.8% of error in clinical cases, especially when events of atrial fibrillation occur (Bae et al 2012). Therefore preliminary software interpretations require reading and confirmation by a qualified eletrocardiographer (Estes 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Box 2 shows the common differentials for atrial fibrillation that are reported on ECG. (10,11) In conclusion, the ECG, like all other investigations, should always be interpreted in relation to the patient and the clinical scenarios. The computer is not, and should not be, a surrogate for a physician's knowledge and clinical acumen but, when utilised appropriately, can certainly be a useful aid in clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…Data-driven Versus Hypothesis-driven Research pacemaker artefacts, comorbidities affecting the ECG or medication affecting the rhythm or conduction, might influence the performance of DNNs. [13][14][15][16][17][18] Instead of true disease characteristics, ECG changes due to clinical interventions are used by the DNN to classify ECGs. For example, a DNN using chest X-rays provided insight into long-term mortality, but the presence of a thoracic drain and inadequately labelled input data resulted in an algorithm that was unsuitable for clinical decision-making.…”
Section: Threats Of Artificial Intelligence In Electrophysiologymentioning
confidence: 99%